2006
DOI: 10.1080/01443610600747140
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the referral patterns to a vulval clinic: highlighting educational needs in this subspecialty

Abstract: A retrospective study of the referral patterns to a specialist vulval clinic was performed. A total of 200 clinical records were reviewed of new patients seen between January 2004 and June 2005. A provisional diagnosis was stated in 45.5% of referrals, of which 27.5% had the diagnosis changed at the clinic. The majority of referrals were from general practitioners (GPs) (77%) and smaller proportions from gynaecologists (11%), dermatologists (9%) and others (3%). The most common conditions seen were lichen scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
1
16
3
1
Order By: Relevance
“…The prevalence of AGLSC was about 0.5% in the general population of the western Europe and America, [1] 10% in a study in a multidisciplinary vulvar clinic, [3] 30.5% in a specialist referral vulvar clinic [4] and 35% among non-neoplastic vulvar biopsies. [5] In our study, the frequency of AGLSC among patients attending the Dermatology OPD was 1.44 per 1000 population.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of AGLSC was about 0.5% in the general population of the western Europe and America, [1] 10% in a study in a multidisciplinary vulvar clinic, [3] 30.5% in a specialist referral vulvar clinic [4] and 35% among non-neoplastic vulvar biopsies. [5] In our study, the frequency of AGLSC among patients attending the Dermatology OPD was 1.44 per 1000 population.…”
Section: Discussionmentioning
confidence: 99%
“…La localisation des dermatoses génitales chez les femmes prédominent au niveau des grandes et petites lèvres dans notre série ce qui rejoint l’étude indienne à propos de 120 patients avec un pourcentage de 92% au niveau des grandes lèvres et 48% au niveau des petites lèvres [2]. Les dermatoses génitales retrouvées chez les femmes dans notre étude sont prédominées par les dermatoses d'origine virale suivie par le vitiligo puis l'origine mycosique, cela n'est pas le cas dans la littérature où elles sont prédominées par le lichen scléreux suivi par le vitiligo puis l'origine mycosique et les autres étiologies [2, 6, 7]. …”
Section: Discussionunclassified
“…These finding were comparable to a similar study conducted by Deeptara Pathak et al 6 The commonest presenting complaint in our study was vulvar itching (60%) which was in concordance with other studies except for a study conducted by Harlow et al who found vulvar pain to be the commonest presenting symptom seen in nearly 12% of patients followed by itching and burning in 6.6% of patients. [6][7][8][9] The most common group of vulvar dermatoses noted in our study was infections and infestations seen in 50 patients (71.42%), followed by inflammatory dermatoses in 20%, benign tumors and cysts in 5.7%. The incidence of these dermatoses was similar to that observed in a study conducted in Nepal but was in contrast to the study…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is in contrast to studies quoted in western literature where lichen sclerosus et atrophicus was the most most frequently observed vulvar dermatoses. 8,11,12 The reason for this variation could be due to the age group of patients in our study which mainly comprised of women of reproductive age group, while it has been mentioned in medical literature that LSA has two peak ages of presentation: prepubertal and post-menopausal. A study of 350 women with LSA by Thomas et al showed that the mean age of patients was 56 years.…”
mentioning
confidence: 94%
See 1 more Smart Citation